2001
DOI: 10.1149/1.1413991
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Voltammetric Responses of Toluene and Xylenes at Iron(III)-Doped, Bismuth(V)-Doped, and Undoped β-Lead Dioxide Film Electrodes in 0.50 M H[sub 2]SO[sub 4]

Abstract: Voltammetric activities are compared for the designated compounds in 0.50 M H 2 SO 4 at the specified film electrodes configured as rotated disks. The effective number of electrons ͑n eff , equiv mol Ϫ1 ͒ calculated from the Koutecky-Levich plot is 3.1 Ϯ 0.2 for toluene oxidation at the Fe-PbO 2 electrode, compared to 2.0 Ϯ 0.05 and 4.1 Ϯ 0.3 at the Bi-PbO 2 and PbO 2 electrodes, respectively. Gas chromatography-mass spectrometry data confirm that the primary product of toluene oxidation is benzyl alcohol ͑2 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…It has also been reported that the activity and stability of PbO 2 anodes may be significantly improved by the incorporation of dopants such as Fe 3+ , Bi n+ , Co 2+ and mixtures like Fe-F [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that the activity and stability of PbO 2 anodes may be significantly improved by the incorporation of dopants such as Fe 3+ , Bi n+ , Co 2+ and mixtures like Fe-F [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism for the electrochemical oxidation of organics, based on intermediates of oxygen evolution reaction in aqueous media, was formerly proposed by Johnson (Feng & Johnson, 1990;Vitt & Johnson, 1992;Feng et al, 1994;Treimer et al, 2001). The process involves anodic oxygen transfer from H 2 O to organics via hydroxyl radicals formed by water electrolysis.…”
Section: Electrochemical Oxidation Mechanismmentioning
confidence: 99%
“…4, no significant OH formation was observed in aqueous Fe 0 dispersion (curve a), while the quantities of OH increased with the reaction time (curve b) in aqueous Fe-200 suspension under otherwise identical conditions. According to the published works, in the oxidative electrochemical processes, the initial step is the discharge of water molecules to form adsorbed OH at the anode surface whether O 2 exists or not [19][20][21]. Higher oxidation states on the surface of electrodes are present above the thermodynamic potential from H 2 O to OH, which is lower than 1.23 V from H 2 O to oxygen [22].…”
Section: Characterization Of Catalystsmentioning
confidence: 99%